2017
DOI: 10.1161/circimaging.116.005706
|View full text |Cite
|
Sign up to set email alerts
|

Global Longitudinal Strain and Left Atrial Volume Index Provide Incremental Prognostic Value in Patients With Hypertrophic Cardiomyopathy

Abstract: GLS and LAVI are independently associated with adverse outcome in patients with hypertrophic cardiomyopathy and may help to optimize risk stratification in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 34 publications
1
51
0
2
Order By: Relevance
“…GLS was also a marker of ventricular arrhythmias [39] and was independently associated with adverse cardiovascular outcomes in HCM [69]. A recent study concluded that a reduction of GLS À15% represented patients with better survival in HCM and suggested that GLS should be considered a valuable subclinical biomarker to be incorporated in the standardised risk stratification workup of HCM patients [70].…”
Section: Hypertrophic Cardiomyopathiesmentioning
confidence: 99%
“…GLS was also a marker of ventricular arrhythmias [39] and was independently associated with adverse cardiovascular outcomes in HCM [69]. A recent study concluded that a reduction of GLS À15% represented patients with better survival in HCM and suggested that GLS should be considered a valuable subclinical biomarker to be incorporated in the standardised risk stratification workup of HCM patients [70].…”
Section: Hypertrophic Cardiomyopathiesmentioning
confidence: 99%
“…Left ventricular function abnormalities, even without overt structural changes in the heart, can be a marker of sudden death. Larger left atrial volume index, longer mechanical dispersion indices, and decreased global longitudinal peak strain are markers for appropriate implantable defibrillator shocks in patients with HCM . Lower values of 2D speckle tracking‐derived end‐systolic peak longitudinal strain is described as a predictor of nonsustained ventricular tachycardia and SCD in patients with HCM .…”
Section: Functional Abnormalitiesmentioning
confidence: 99%
“…Larger left atrial volume index, longer mechanical dispersion indices, and decreased global longitudinal peak strain are markers for appropriate implantable defibrillator shocks in patients with HCM. 15,16 Lower values of 2D speckle tracking-derived end-systolic peak longitudinal strain is described as a predictor of nonsustained ventricular tachycardia and SCD in patients with HCM. 17 Advanced LV diastolic dysfunction like restrictive LV filling is a strong predictor of sudden death in HCM.…”
Section: Fun C Tional Ab Normalitie Smentioning
confidence: 99%
“…Second, we were unable to obtain biochemical values or use another imaging method to correlate these associations with our findings and conduct a follow-up of these subjects to assess prognosis and cardiac complications. (10)(11)(12)(13) 12 (10-13) 10 (9-13) 10 (9-11.2) 0.010 E/e' 7.9 (6.5-9.9) 9.3 (7.9-11.9) 11.6 (9.7-14.…”
Section: Strengths and Limitationsmentioning
confidence: 99%